Cyanidin-3-O-Sambubioside from Acanthopanax sessiliflorus Fruit Inhibits Metastasis by Downregulating MMP-9 in Breast Cancer Cells MDA-MB-231 - Lee, Sang-Jin; Hong, Sungyoul; Yoo, Sang-Ho; Kim, Gye-Won (Planta Medica, 2013)
Anthocyanins play an important role in physiological functions related to human health. This study aimed to investigate the inhibitory effect of cyanidin-3-O-sambubioside isolated from Acanthopanax sessiliflorus fruit on cancer cell metastasis. The inhibitory effect of cyanidin-3-O-sambubioside on angiogenesis was assessed by chorioallantoic membrane and tube formation assays. Cyanidin-3-O-sambubioside interrupted the formation of neovasculature and tube-like structures in a dose-dependent manner. It inhibited the wound healing migration and invasion of MDA-MB-231 cells through reconstituted extracellular matrix (Matrigel). Gelatin zymography revealed that cyanidin-3-O-sambubioside significantly decreased the secretion of matrix metalloproteinase-9 and inhibited matrix metalloproteinase-9 expression. In additional, cyanidin-3-O-sambubioside exerted an inhibitory effect on Akt phosphorylation. These results suggest that cyanidin-3-O-sambubioside inhibits metastasis processes, such as angiogenesis and invasion, in breast cancer cells through regulation of matrix metalloproteinase-9 activity.
Keywords: angiogenesis; cancer metastasis; cyanidin-3-O-sambubioside; fruit of Acanthopanax sessiliflorus; Araliaceae; invasion; MMP-9